Knowledge discovery, knowledge engineering and knowledge management : 8th International Joint Conference, IC3K 2016, Porto, Portugal, November 9-11, 2016, Revised selected papers /: 8th International Joint Conference, IC3K 2016, Porto, Portugal, November 9-11, 2016, Revised selected papers. ([2019]) - Unknown
No abstract available